ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING DALAM PENETAPAN HARGA JUAL PADA UD. ELFANA MEUBEL - Dahlya, Elsa Dinalya; Sabarudin; Bustang (Komunitas Manajemen Kompetitif, 2025)
The main purpose of this research determining the costs of production applying full cost pricing to set the selling price at UD. Elfana Meubel. This study employs this study adopted a descriptive qualitative approacch, gathering data through observation, interviews, and document analysyis. The calculation analysis of production costs the full costing method, the following are included all elements off manufacturing costs, comprise raw, material expense, direct workforce expenses, and both fixed and variable factory overhead costs. The results show that applying the Full Costing method provides a more accurate production cost calculasion versus company's previous method. By implementing the Full Costing method, UD. Elfana Meubel can set more competitive selling prices, improve production efficiency, and optimize profitability. This study also recommends that the company enhance financial record-keeping, control overhead costs, and conduct periodic evaluations of its product pricing.process.